Odyssey of Helicobacter pylori:Routes, Meetings, Chronologies - (:unkn) unknown (My University, 2024)
Leaving Africa, the first Homo sapiens unintentionally carried with them travelcompanions, whose association persists until today. This work aims to develop aprotocol of comparative genomics that allows the evolutionary history of contemporarysymbiotic bacteria to highlight contacts between past human populations.We relied on Helicobacter pylori, a bacterium associated with humans for 100,000years, which has accompanied them throughout their movements. Today, the bacteriumis present in one out of two people, with a prevalence that varies according toregions of the world. Interestingly, the strains have structured into genetic groupscharacteristic of human populations established in different geographical areas. Mywork consisted of evaluating the interest of comparative genomics tools adapted tobacteria, to narrate the history of migrations, contacts, and periods of mobility ofthis symbiotic couple.Until now, the co-dispersion between H. pylori and humans has been supported bygenetic studies using 7 MLST marker genes. The phylogenies previously reconstructedsuggest a gradual progression of this tandem from Africa to Asia and then toEurope. We focused in particular on the genetic group hpEurope, characteristic ofEuropean human populations, described as an emerging group resulting from hybridizationof two ancestral populations AE1 and AE2.However, our phylogenetic analysis results, based on H. pylori’s universal genes,contradict this scenario and lead us to reassess the idea of strict co-dispersion.hpEurope does not appear to be an emerging group resulting from a mixture, butrather a genetic group that structured early after leaving Africa, with a separationof European strains into two lineages that followed distinct evolutionary histories.One lineage is characteristic of northern Europe where a clade containing all currentAsian strains emerges, while the other is characteristic of southern Europe wheregroups of African strains that returned to Africa s
Keywords: African Research